Growth Performance and Osmoregulation of Vaname Shrimp (Litopenaeus Vannamei) with Cultivation Media Engineering - Aldy Eka Wahyudi; Abdul Rahem Faqih; Sri Andayani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Production of white shrimp (Litopenaeus vannamei) in 2024 is targeted by the Ministry of Fisheries and Marine Affairs to be increased by producing 2 million tons / year. However, in fact, in 2022 white shrimp production is 1.09 million tons, so to achieve the target, new technology and innovation are needed. The obstacle experienced with freshwater cultivation is the low mineral that plays an important role in the growth of white shrimp. To be able to cultivate white shrimp in fresh water, it is necessary to first conduct a study on the manipulation of aquaculture water with freshwater, salt and bittern components as mineral sources. The purpose of this study is to test the combination of components of artificial water media for white shrimp farming and analyze the mineral content. The study will be conducted from March to April 2024. The method used is an experimental method with Completely Randomized Design (CRD). Data collection is carried out by field observation and literature study. The research procedures carried out were bittern and salt collection and white shrimp sampling, media preparation, mineral test on water as culture media, white shrimp stocking, white shrimp rearing, morphology and survival rate tests and viscosity tests to review osmoregulation in white shrimp and data analysis. Data analysis was performed using Canonical Correlation Analysis (CCA) with PAST 4.03 software. The mineral content produced is directly proportional to the amount of dose given. The best dose of bittern in this study is in treatment C with a dose of 15 ml which has a calcium content of 45.2 mg/L, magnesium 155 mg/L, and potassium 73.89 mg/L.